Growth performance, carcass composition, physico-chemical traits and amino acid profile of meat depending on wormwood (Artemisia absinthium L.) dietary supplementation in broilers - D. Zapletal; R. Dobšíková; V. Šimek; J. Kameník; F. Ježek (Archives Animal Breeding, 2024)
The present study was conducted to determine the effect of dietary inclusion of the wormwood (Artemisia absinthium L.) meal on growth performance, carcass composition, physico-chemical traits and amino acid profile in meats of fattened broilers. In a completely randomised block design, a total of 288 female broilers that were 21 d old (Ross 308) were divided into four dietary groups and fed for 3 weeks: the control basal broiler diet (C), without any anticoccidial or wormwood herb (WH) supplementation, and the C diet plus 10 g (WW1 group), 50 g (WW5 group) or 100 g (WW10 group) of WH meal supplementation per kilogram of basal diet. At the end of the experiment (day 42), broilers were randomly selected for carcass composition and meat quality trait evaluation. In conclusion, the final live weight of chickens was not affected by diets with higher WH levels (P>0.05). For the entire experimental period, the feed conversion ratio raised with an increasing WH level in diets, showing the highest value in chickens of the WW10 group (P<0.01). Dietary supplementation with wormwood (WW) had no negative effects on the carcass composition or on the chemical and physical traits of meat quality assessed. By contrast, it can be assumed that WH dietary supplementation influenced, predominantly, proteosynthesis of chickens, resulting in alteration of amino acid profiles in meats, where especially increasing aspartic acid and valine contents (P<0.001) in the leg meat were found. Our findings indicate that the supplementation of 5 % WH to the diet showed favourable results for chicken performance. However, it is necessary to conduct further studies dealing with WH dietary effects on metabolism and heath control in chickens.